Pengaruh Manajemen Waktu Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PPKN Di SMA Swasta Gajah Mada - Donna Jesika Gulo; Maryatun Kabatiah (CV. ULIL ALBAB CORP, 2024)
This research was motivated by students' difficulties in managing their study time well and regularly, this was because students did not have a schedule as a reference for their daily activities. The existence of management elements in the learning process will make learning more organized. Researchers use quantitative research with a correlational approach. In this research, which uses quantitative methods, the variable that is not influenced is study time management, while the variable that is influenced is learning outcomes. The population in this study consisted of all class XI students at Gajah Mada Private High School, totaling 39 people.The results of the research show that study time management influences student learning outcomes in class for Civics subjects at SMAS Gajah Mada Medan, namely obtained tcount of 16.421 and ttable of 1.687 or 16.421 > 1.687 and a significant value of study time management of 0.000 <0.05 (H0 is rejected and H1 is accepted). This can be seen from the simple regression test data at the sig level. It was found that the sig value of the study time management variable was 0.000 in accordance with the provisions used if the significance of r calculated > α = 0.5 then H0 was accepted. Because the sig value, (rcount) obtained is 0.000 < 0.05, Hα is accepted, it can be concluded that study time management influences the learning outcomes of class XI students in Civics subjects at SMAS Gajah Mada Medan.